Dictionary of business and economics - Ammer, Christine; Ammer, Dean S. (New York : Free Press ; London : Collier Macmillan, 1977)
The entries in this dictionary cover an extraordinary broad range, form economic theory of the past and present to its numerous applications in the world of business firms, and consumers, from price and income theory to real estate, insurance, business law, and accounting, from public finance and labour economics to the world of the small investor.
Includes bibliographical references: p. 459-461.
ne 01/09/2021
Ref.
Keywords: Economics; Business